Flow- Shop scheduling Problem to Minimize Total Weighted Late Work - M. K., Al Zuwaini; T. S., Abdul Razaq; S. K., Al Saidy (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
In this paper we considered a flow-shop scheduling problem to minimize the total weighed late work. Branch and bound method was suggested to obtain an optimal solution. Several local search methods: descent method, simulated annealing, threshold accepting, genetic algorithm and hybrid method were used to obtain near optimal solutions, and comparison the results.